Pengembangan Kurikulum Merdeka terhadap Perubahan dan Kebutuhan DUDIKA - Amal Purnomo; Annisa Fajria Maulida; Dyah Fitriana Lukitasari; Triana Sayekti Peni Puji Lestari; Verra Prastika; Ngurah Ayu Nyoman Murniati (Universitas Ngudi Waluyo, 2025)
Abstract Curriculum development is a key element in improving education quality, especially in vocational schools like SMK Negeri 1 Wirosari. This study aims to analyze the implementation, evaluation, and development strategies of curriculum relevant to the needs of the workforce and students’ characteristics within the Merdeka Curriculum framework. A descriptive-qualitative literature review approach was used to examine curriculum development models such as Tyler, Taba, and Wheeler, alongside theories from Bloom and Freire. The findings reveal that the Merdeka Curriculum offers flexibility for teachers to design project-based and contextual learning. Best practices include teaching factory programs like Wira Bakery in the APHP department and strategic collaboration between the Automotive Engineering department and Yamaha Harpindo Wirosari. Furthermore, active teacher involvement in module development and authentic assessments strengthens curriculum relevance. However, infrastructure limitations, teacher readiness, and uneven implementation across departments remain significant challenges. Therefore, adaptive, collaborative, and continuously evaluated curriculum management is essential to realize vocational education that responds effectively to changing demands and the needs of the business and industrial sectors. Abstrak Pengembangan kurikulum merupakan elemen kunci dalam peningkatan mutu pendidikan, terutama di satuan pendidikan kejuruan seperti SMK Negeri 1 Wirosari. Penelitian ini bertujuan untuk menganalisis implementasi, evaluasi, dan strategi pengembangan kurikulum yang relevan dengan kebutuhan dunia kerja dan karakteristik peserta didik dalam bingkai Kurikulum Merdeka. Pendekatan deskriptif-kualitatif melalui studi pustaka digunakan untuk mengkaji model pengembangan kurikulum seperti Tyler, Taba, dan Wheeler, serta gagasan dari Bloom dan Freire. Hasil studi menunjukkan bahwa Kurikulum Merdeka memberikan fleksibilitas kepada guru dalam menyusun pembelajaran berbasis proyek dan kontekstual. Praktik baik ditunjukkan melalui program teaching factory seperti Wira Bakery di jurusan APHP dan kerja sama jurusan Teknik Otomotif dengan Yamaha Harpindo Wirosari. Selain itu, pelibatan guru dalam pengembangan modul dan asesment autentik memperkuat relevansi kurikulum. Namun, keterbatasan infrastruktur, kesiapan guru, dan kesenjangan implementasi antar jurusan menjadi tantangan utama. Oleh karena itu, dibutuhkan manajemen pengembangan kurikulum yang adaptif, kolaboratif, dan berbasis evaluasi berkelanjutan untuk mewujudkan pendidikan vokasional yang responsif terhadap perubahan dan kebutuhan DUDIKA.